The Effects of Fe Tablets and Ambon Banana towards Hemoglobin Levels to Female Teenagers - Luluk Handayani; Rini Sulistiawati; Vera Renta Siahaan (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
The prevalence of anemia in Indonesia reaches 18.4% at the age of 15 to 24 years. Female tenagers are prone to anemia due to growth spurt and loss of iron levels of about 12.5 to 15 mg during menstruation. Efforts to counter anemia are done by administering fe tablet. Fe tablet absorption works well when accompanied with food that contains a good amount of vitamin C and iron, such as Ambon banana. This research aims to determine the effects of fe tablets and Ambon banana to increase levels hemoglobin levels on anemic female teenagers.This research was a quasy experiment with pre test and post test non equivalent control group design non randomize. Research population are female teenagers from in the Midwifery Dormitory of Poltekkes, Ministry of Health Pontianak. The sample collecting method is purposive sampling, totals of samples as 30 samples consisting of 15 interventions and 15 controls. Data analysis using paired t-test and mann-whitney. The Result of this research is increase in hemoglobin levels in the intervention group was 1.2 g/dL higher than the control group was 0.3 g/dL. The result of statistical test was 0.001 (P0.05) so there was an effect of Fe tablets and Ambon banana towards on hemoglobin levels on anemic female teenagers.Vitamin C contained in Ambon bananas can increase iron absorption, so consuming Ambon bananas with Fe tablets can increase hemoglobin levels.